The limits of "multiculturalism without diversity": multi-ethnic students and the negotiation of "difference" in South Korean schools. Issue 5 (8th April 2020) - Walton, Jessica
ABSTRACT: Since 2006, although South Korean "multiculturalism" policies have attempted to grapple with increasing ethnic and cultural diversity within Korean society, a homogenous national imaginary continues to inform these policies. I refer to the government's approach to multiculturalism as "multiculturalism without diversity" to describe the limits of a multiculturalism anchored within an ethnic nationalistic framing of "difference". Based on findings from an ethnographic study in South Korean primary schools, this paper examines how tensions between the reality of increasing diversity and a multicultural policy approach that maintains homogenous representations of Korean identity played out among Grade 5/6 children from Korean mono-ethnic and multi-ethnic backgrounds. Although there were limits to the ways children could assert authority, this paper analyses the mundane everyday practices and strategies that multi-ethnic children used to attempt to reassert and reinsert themselves at school and more broadly, within the possibility of a more critical Korean multiculturalism.